Decision-Making Algorithm for the Issuance of the Green Bonds by Municipalities in Inter-Municipal Cooperation in Lithuania - Julija Bužinskė; Jelena Stankevičienė (Economies, 2023)
The objective of this study is to establish a decision-making algorithm for issuing green bonds by municipalities in inter-municipal cooperation in Lithuania with a focus on zero-waste projects. The research methodology comprises four parts. The first part of the research methodology corresponds to a literature review that examines the concept of inter-municipal cooperation and its development in different countries. The second part of the research methodology is dedicated to the formulation of the valuation approach for the inter-municipal cooperation possibility and approbation of it in the selected municipalities. The third part of the research methodology covers the development of the decision-making algorithm for issuing green bonds by municipalities in inter-municipal cooperation in Lithuania. The last part of the research methodology summarizes the results of the survey and proposals for its further development. The findings suggest that the selected municipalities for the valuation of inter-municipal cooperation possibility could improve municipal performance for better inter-municipal cooperation results. The results also show that a smaller municipality corresponds to moderate municipal performance, which can be expected in comparison to a larger municipality. The findings of the construction of the decision-making algorithm suggest a 12-step process for the issuance of green bonds in Lithuania. The practical implications of the study are based on the notion that findings can be applied by municipalities willing to issue green bonds, smaller municipalities having challenges finding financial sources, and municipalities in inter-municipal cooperation sharing the same goals. An original aspect of this paper is its study focus on inter-municipal cooperation valuation and the issuance of green bonds in the municipalities of a smaller country which can serve as a reference point for considering the potential issuance of green bonds in municipalities of similar size.